The Sensitivity of Islamic Banking Stock Prices During the Pandemic Covid-19 - Efi Syarifudin; Nani Nani; Anggita Nurcahyani (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Economic growth has contracted due to the COVID-19 pandemic. Based on the history of previous economic and financial crises, the banking sector is one of the most sensitive sectors during a crisis. Investors consider these conditions for their investment decisions. This paper aims to find the factors that determine the stock price of Islamic banking on three observation variables: profit, debt equity ratio (DER), and cash flow from operating (CFO). This study used a quantitative approach with secondary data sources from financial statements and company stock prices. The sample was selected purposively from Islamic banking stocks listed on the Indonesian Sharia Stock Index (ISSI). Data analysis used panel data regression using the E-Views 10 application. The findings of this study are that earnings and DER significantly determine the share price of Islamic banking based on a partial test. Profit has a positive effect, while DER has a negative impact. These findings illustrate that expectations for investment in Islamic banking stocks remained stable during the pandemic. The company's fundamental factors determine the demand for Islamic bank shares.